The intensified leaching mechanism of phosphorus-potassium associated ore in HCl-CaF2 system with sodium dodecyl sulfate - Liu, Cuncheng; Wang, Weiguo; Yang, Fan; Ma, Jiayu; Yang, Wenqi; Wang, Tielin; Wang, Cunwen (Chemical engineering and processing, 2020)
The schematic diagram of intensified leaching process of phosphorus-potassium associated ore in HCl-CaF2 system with SDS. [Display omitted] •Effect of sodium dodecyl sulfate on leaching solution surface tensions and specific viscosities was determined.•The enhanced potassium leaching mechanism of phosphorus-potassium associated ore with sodium dodecyl sulfate was elucidated.•An intensified leaching process schematic diagram of the ore in HCl-CaF2 media with sodium dodecyl sulfate was developed. The enhanced potassium leaching mechanism of phosphorus-potassium associated ore with sodium dodecyl sulfate (SDS) was systematically elucidated and attributed to the combined effects such as the wetting, adsorption, dispersion and permeation actions. First, the formation of the adsorption film with 1.25 g L−1SDS led to the surface tension and the contact angle obviously decreased, promoting the wetting, dispersion and permeation actions. Second, more acid and fluorine entered into the interior of the ore due to the enhanced molecular and convective diffusions and the enlarged fissures and particle size of the ore, leading to higher potassium dissolution fraction. However, much micelle covering on the residue fixed layer would be formed if 5.00 g L−1 SDS exceeded the critical micellization concentration (CMC), which hindered acid and fluorine entered into the interior, indicating decreased potassium dissolution fraction. Finally, an intensified leaching process schematic diagram of the ore in HCl-CaF2 media with SDS was developed. These novel findings demonstrate that SDS can enhance effectively and obviously the leaching of potassium from phosphorus-potassium associated ore. In addition, the intensified leaching mechanism by SDS will be helpful for efficient extraction, enrichment and utilization of mineral resources.